2014
DOI: 10.1534/genetics.113.156281
|View full text |Cite
|
Sign up to set email alerts
|

Dual Phosphorylation of Cdk1 Coordinates Cell Proliferation with Key Developmental Processes in Drosophila

Abstract: Eukaryotic organisms use conserved checkpoint mechanisms that regulate Cdk1 by inhibitory phosphorylation to prevent mitosis from interfering with DNA replication or repair. In metazoans, this checkpoint mechanism is also used for coordinating mitosis with dynamic developmental processes. Inhibitory phosphorylation of Cdk1 is catalyzed by Wee1 kinases that phosphorylate tyrosine 15 (Y15) and dual-specificity Myt1 kinases found only in metazoans that phosphorylate Y15 and the adjacent threonine (T14) residue. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 69 publications
2
43
0
Order By: Relevance
“…We found that reduced Cdk1 activity partially rescued the short-sleeping phenotypes of tara and CycA mutants, 9 suggesting that Cdk1 is a wake-promoting molecule. Since Cdk1 is regulated through inhibitory phosphorylation of its T14 and Y15 residues, we employed a mutant Cdk1-AF (T14A, Y15F) that cannot be inhibited 24 to show that increased activity of Cdk1 suppresses sleep. Given that CycA and Cdk1 are known to physically interact, 23 a direct relationship between CycA and Cdk1 for sleep regulation is likely.…”
mentioning
confidence: 99%
“…We found that reduced Cdk1 activity partially rescued the short-sleeping phenotypes of tara and CycA mutants, 9 suggesting that Cdk1 is a wake-promoting molecule. Since Cdk1 is regulated through inhibitory phosphorylation of its T14 and Y15 residues, we employed a mutant Cdk1-AF (T14A, Y15F) that cannot be inhibited 24 to show that increased activity of Cdk1 suppresses sleep. Given that CycA and Cdk1 are known to physically interact, 23 a direct relationship between CycA and Cdk1 for sleep regulation is likely.…”
mentioning
confidence: 99%
“…Microchaete pI cells are specified in early pupal stages but then arrest in G2 phase for almost 10 h until the mitotic cycles begin (Hartenstein and Posakony, 1989;Huang et al, 1991;Usui and Kimura, 1992). To investigate how G2 phase arrest affected SO development, we used Gal4-driven expression of a transgenic Cdk1 phospho-acceptor mutant that efficiently bypasses developmental G2 phase checkpoint arrest (Ayeni et al, 2014). Genetic crosses with a neur p72 -Gal4 strain were used to express Cdk1 Y15F -VFP (hereafter called Cdk1F) or wildtype Cdk1-VFP (as a control, hereafter called Cdk1WT) in arrested SO progenitor cells, several hours before they would normally divide (Bellaïche et al, 2001;Parks et al, 1997).…”
Section: Premature Pi Cell Division Results In Sos With Supernumerarymentioning
confidence: 99%
“…Moreover, unlike Cdk1F, overexpression of Cdc25 stg usually induced apoptosis in the Ttk + posterior pI daughter cell. In these respects, ectopic Cdc25 stg behaves more like expression of a non-inhibitable Cdk1 T14A,Y15F mutant, which causes gross chromosomal abnormalities, in addition to bypass of G2 phase checkpoint arrest (Ayeni et al, 2014). Alternatively, other factors affected by Cdc25 stg might explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations